Many touched by MacGowan's Music - Rich, Doug (Raton, NM Raton Range, 1998)
This article is about Madonna MacGowan and the end of her playing for the Churches around town.
Newspaper article
Mater List Item # 16
File location is in the Raton File Cabinet
Keywords: MacGowan, Madonna; MacGowan, Arch; First United Methodist Church; First Presbyterian Church; Church Music; Music; Keyboards; Organist; Retirement; Raton, New Mexico